2012
DOI: 10.1007/s10157-012-0663-x
|View full text |Cite
|
Sign up to set email alerts
|

Virological responses of pegylated interferon alpha-2a treatment in hemodialysis patients infected with hepatitis C

Abstract: According to results of this study, patients achieved good sustained viral and biochemical response rates with Peg-IFN-α-2a treatment. Histology activity index may be a predictor for SVR; but large randomized controlled trials are needed. Weekly 135 mcg dose of Peg-IFN-α-2a for 48 weeks is an effective treatment in HCV-infected hemodialysis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
0
5
0
1
Order By: Relevance
“…Sixteen reports were excluded because they contained duplicate reports of the same patients ( N = 2) and did not fulfill the inclusion criteria ( N = 14). A total of 24 reports giving information on 744 unique patients undergoing long‐term dialysis were included in our meta‐analysis . There was a 100% concordance between reviewers with respect to final inclusion and exclusion of studies reviewed based on the predefined and exclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
“…Sixteen reports were excluded because they contained duplicate reports of the same patients ( N = 2) and did not fulfill the inclusion criteria ( N = 14). A total of 24 reports giving information on 744 unique patients undergoing long‐term dialysis were included in our meta‐analysis . There was a 100% concordance between reviewers with respect to final inclusion and exclusion of studies reviewed based on the predefined and exclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding IFN monotherapy in hemodialysis patients with chronic HCV infection, there are limited data in Turkey provided from studies of small series, and SVR rates vary between 46.1-75% in these series. Apart from our case report, we could not encounter a study subjecting ribavirin or protease inhibitor usage in hemodialysis patients in Turkey [3,[19][20][21][22] .…”
Section: Discussionmentioning
confidence: 99%
“…The same treatment response rate of 50% was reported by Kose et al PEG IFNa-2a as a monotherapy (135 mg/weekly) was given to 38 hemodialysis patients with chronic hepatitis C for 48 weeks. 29 There was no other published study about the association between the IL28B gene polymorphisms and response to HCV infection treatment in hemodialysis patients. Yu et al identified association of one polymorphism (rs8099917) and HCV infection clearance in hemodialysis patients, but the clearance of HCV infection was spontaneous, and not treatment induced as it was in our study.…”
Section: Disscusionmentioning
confidence: 99%
“…Recent studies of hepatitis C treatment in hemodialysis patients, with PEG IFNa-2a, included between 13 and 40 patients. 29,[34][35][36] However, it has to be taken into consideration that roughly 20% of the treated patients with favorable CC genotype of rs12979860 did not achieve SVR, 37 due to dynamic interactions between genes or between genes and environment. 38 Other factors such as ethnicity and HCV genotype should be used together with IL28B genotype as pretreatment predictors for response.…”
Section: Disscusionmentioning
confidence: 99%